The trajectory of PTSD among youth in foster care: A survival analysis examining maltreatment experiences prior to entry into care. (May 2021) - McGuire, Austen; Huffhines, Lindsay; Jackson, Yo
Abstract: Background: Youth in foster care are more likely than non-foster care youth to experience posttraumatic stress disorder (PTSD). While research has identified maltreatment as a risk factor for PTSD, this research remains limited because it tends to only (a) examine a single type or dimension of maltreatment and ignore the polyvictimization and heterogeneity in exposure, and (b) study this relation across a short period time or retrospectively at the end of care. Objective: The current study used survival analysis to simultaneously examine the influence of maltreatment characteristics on the risk of receiving a PTSD diagnosis at any time in care following entry into care. Participants/Setting: : 291 youth ( Mean age at entry = 9.71; 53 % female; 49 % Black) in foster care and their primary caregivers from a large, Midwestern county. Methods: Information on PTSD diagnosis was extracted from Medicaid records, and information on maltreatment and time in care was extracted from case files. Survival analysis was then used to determine the association between maltreatment and risk of PTSD diagnosis. Results: When examined independently, each dimension (frequency, severity) of the four maltreatment types was significantly associated with PTSD diagnosis risk (all hazard ratio's [HR] > 1.00), except sexual abuse frequency. In the comprehensive model with all dimensions examined simultaneously, only neglect frequency for youth entering care in adolescence (HR: 1.13[1.03−1.23]), and neglect severity (HR: 1.27[1.05−1.52]) and emotional abuse frequency (HR: 1.24[1.00−1.53]) for youth entering care pre-adolescence, were associated with PTSD diagnosis risk. Additionally, age of entry into care was associated with PTSD diagnosis risk (HR: 2.34[1.88−2.92]), as adolescents tended to spend fewer days in care before receiving a diagnosis. Conclusions: Results suggest that researchers who study PTSD in youth in foster care should consider the entirety of youth's maltreatment exposure and the context of care to more accurately determine what aspects of youth's history contributes to receiving a PTSD diagnosis.